Knowledge and Attitude of Nurses about Nursing Ethical Principles at the Trikora Salakan Regional General Hospital Banggai Regency Central Sulawesi Province - Ni Ketut Elmiyanti; Retsiola Kinait; Chely Veronica Mauruh; Niswa Salamung; Freny Ravika Mbaloto (Universitas Bondowoso, 2021)
Introduction: The ethical principles of nursing consist of autonomy, beneficial, justice, non maleficience, veracity, fidelity, confidentiality and accountability. Based on observations made by researchers at the hospital, that there were 6 nurses who leaked the patient's identity, then the researcher asked 6 nurses whether it was necessary to explain to the patient when taking action the nurse said it was not necessary. The purpose of this study was to determine the knowledge and attitudes of nurses about the principles of nursing ethics at the Trikora Salakan General Hospital, Banggai Islands Regency, Central Sulawesi Province. Method: This type of research is descriptive which aims to determine the knowledge and attitudes of nurses about the ethical principles of nursing. This type of data uses primary data and secondary data. Collecting data using a questionnaire with 25 assessment items with knowledge and attitudes. Data analysis used univariate analysis. The population in this study were nurses in the inpatient room of the Trikora General Hospital, Salakan. The sample in this study were all implementing nurses in the inpatient room at Trikora General Hospital Salakan with a total sample of 52 respondents. Result: Showed that the knowledge of good by 82 , 7 %, enough knowledge as much as 17.3%, while as much as 76.9% good attitude, the attitude of quite as much as 23.1%. It is hoped that nurses can maintain the application of ethical principles to patients so that they feel comfortable in the hospital.